Pembelajaran Matematika Menggunakan Media Benda Konkret (Kancing Baju Dan Sedotan) Untuk Meningkatkan Hasil Belajar - Susilowaty, Nora; angel (LPPM Universitas Advent Indonesia, 2025)
The aim of this research is to improve student learning outcomes in addition and subtraction material by using simple concrete objects, such as shirt buttons and straws. This will be interesting because students will understand it more easily by using real objects around them. This research is classroom action research, involving 15 grade 1 students at Parongpong Adventist Elementary School. This research consists of two cycles, each cycle includes Planning, Implementation, Observation and Reflection. The instruments used were test questions, observation sheets and interviews. The results of the research show that there is an increase in student learning outcomes which can be seen in the average class scores between cycle I and Cycle II respectively, namely 73.50 and 78.01, and the percentage of completeness of student learning outcomes in cycles I and II respectively, namely 73.33% and 86.67%. Based on these results, it can be concluded that learning using clothes buttons and straws can improve students' mathematics learning outcomes